Canopy arthropod responses to experimental canopy opening and debris deposition in a tropical rainforest subject to hurricanes - Schowalter, Timothy D.; Willig, Michael R.; Presley, Steven J. (Forest ecology and management, 2014)
•We examined the effects of canopy opening and debris deposition resulting from hurricanes.•Canopy arthropods were sampled before and after the experimental manipulation.•Canopy trimming did not significantly affect canopy arthropod abundances or diversity.•Abundance of a scale insect increased significantly in debris deposition treatments.•Diversity generally increased in debris deposition treatments. We analyzed responses of canopy arthropods on seven representative early and late successional overstory and understory tree species to a canopy trimming experiment designed to separate effects of canopy opening and debris pulse (resulting from hurricane disturbance) in a tropical rainforest ecosystem at the Luquillo Experimental Forest Long-Term Ecological Research (LTER) site in Puerto Rico. We expected that either canopy opening or added debris would result in increased abundances of certain scale insects and other hemipterans, and thereby affect arthropod diversity. Six of thirteen arthropod taxa tested showed significant responses to treatments as main effects or interactions. No taxon responded significantly to trim treatment alone. The red wax scale, Ceroplastes rubens (on Manilkara bidentata), was significantly less abundant in treatments with added debris than in treatments without added debris, and salticid spiders (on Sloanea berteroana) were significantly more abundant in treatments with added debris than in other treatments. Canopy trimming generally did not have a significant effect on assemblage diversity, whereas debris deposition significantly increased diversity on three late successional tree species. A number of significant treatment interactions were observed. Overall, the debris pulse had a greater effect on canopy arthropods than did canopy opening, suggesting that changes in plant condition resulting from nutrient availability associated with debris deposition have a greater effect on canopy arthropods than do the more direct and immediate changes in abiotic conditions resulting from canopy opening.